Edukasi Penyakit Tuberkulosis dan Pemeriksaan Laboratorium pada Siswa SMA di Kecamatan Bayongbong Garut - Mamay Mamay; Astari Nurisani; Gina Nafsa Mutmaina; Sugiah Sugiah; Muhammad Hadi Sulhan; N Ai Erlinawati (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Mycobacterium tuberculosis is a bacterium that causes the infectious disease pulmonary tuberculosis (TB). Bayongong District is ranked second in terms of TB cases found in Garut Regency. The involvement of adolescents in controlling TB disease is needed as an agent of change to increase early detection of TB in their family members. With early detection of TB disease, treatment can be started quickly and transmission can be controlled. To increase teenagers' knowledge and awareness of TB disease, it is necessary to provide education to teenagers, namely high school students in Bayongbong District, about the importance of recognizing symptoms, transmission, prevention and treatment, as well as laboratory examinations for TB disease. Education is carried out by presenting material related to TB disease. Apart from that, students were also shown a video on how to carry out a TB examination using BTA (Acid Fast Bacteria) staining and TCM (Rapid Molecular Test). Before and after education, each student received a questionnaire designed to measure their level of knowledge. After community service, education about TB disease among high school students resulted in an increased understanding of TB symptoms, transmission, prevention, treatment and examination.